Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

Aleksandr Stepanovich Kuchin: the Russian who went south with Amundsen - Barr, William (Polar Record, 1985)
Aleksandr Stepanovich Kuchin (1888–1912) was already an experienced mariner and oceanographer when Amundsen invited him to join the Fram expedition of 1910–12. Expecting a voyage through the Barents Sea, Kuchin found himself on an expedition to the Antarctic. While Amundsen's sledging parties sought the South Pole, Kuchin remained with the ship, completing an excellent oceanographic survey of the southern Atlantic Ocean. Returning to Russia in 1912 he was recruited, by the geologist and explorer V. A. Rusinov to join a scientific expedition to Svalbard. As deputy leader of the party and captain of Gerkules, the expedition ship, Kuchin played an important role in the Svalbard survey. Then once again found himself heading in an unexpected direction: on completing the Svalbard work, Rusanov decided to attempt the Northern Sea Route to the Bering Strait. Gerkules disappeared and was never seen again; her loss, presumably in the Kara Sea, brought to an untimely end the career of a promising young polar explorer.
Keywords: Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; biografier; oseanografi; polarområdene

Technological transformation in the Norwegian whaling industry in the interwar period - Basberg, Bjørn L (Scandinavian Economic History Review, 1985)
Inventions, innovations and technological changes in the broadest sense are often treated as an independent process and are not subjected to any detailed attempts at explanation. It is scarcely anything exceptional, for example, that Sigurd Risting, the first historian of the whaling industry in Norway, explains the development of whaling as follows: Thus there has been a large stock of finback whales along the coast of Norway for hundreds of years without their having been an object of regular profitable hunting. The reason for this has been nothing more than lack of tackle and methods capable of making hunting possible. The moment these become available, whaling as a rational business will arise by itself out of natural necessity, so to speak." Bjern L. Basberg, b. 1952, is a research fellow in economic history at the Norwegian School of Economic and Business Administration. The article is based on a thesis of 1980 titled: Innovasjons-teori, patenter og teknologisk utvikling i norsk hvalfangst ca. 1860-1968.
Keywords: Norge; Sørishavet; hvalfangst; pelagisk; teknologi; økonomi

Flykatastrofe i antarktisk "white out" - Dannevig, Petter (Været: populærvitenskapelig tidsskrift, 1985)
Keywords: Antarktis; luftfart

Oceanographic conditions on the Weddell Sea Shelf during the German Antarctic Expedition 1979/80 - Foldvik, Arne; Gammelsrød, Tor; Slotsvik, Noralf; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; hydrografi; isshelf; oseanografi

Hydrographic observations from the Weddell Sea during the Norwegian Antarctic Research Expedition 1976/77 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; hydrografi; kontinentalsokkel; observasjoner

Physical oceanography studies in the Weddell Sea during the Norwegian Antarctic Research Expedition 1978/79 - Foldvik, Arne; Gammelsrød, Tor; Tørresen, Tor (Polar Research, 1985)
Keywords: Sørishavet; Weddellhavet; havstrømmer; hydrografi; isshelf; oseanografi

Seismic investigations in the Weddell Sea Embayment - Haugland, Kristen; Kristoffersen, Yngve; Velde, Anders (Tectonophysics, 1985)
Keywords: Antarktis; NARE 1976/77; NARE 1978/79; Weddellhavet; ekspedisjoner; seismologi

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Isfjell og isbreer i Antarktis - Orheim, Olav (Det norske videnskaps-akademi. Årbok, 1985)
Keywords: Antarktis; glasiologi

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

The distribution of lipid in the tissues of Antarctic krill, Euphausia superba - Saether, Olav; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. The distribution of lipid in the tissues of Euphausia superba has been examined by histological and chemical methods. 2. The total lipid content of krill from different catches may vary considerably, and the variations are probably due both to differences in nutritional status and maturity of the roe of female krill. 3. Female krill contained about twice as much lipid as male krill from the same haul. 4. The roe is the dominating lipid depot in female krill; in both male and female krill lipid-rich areas are found along the digestive tract, between muscle bundles and beneath the exoskeleton. 5. Both the phosphoglyceride- and triacylglycerol content of body fractions of E. superba varied in proportion to the total lipid content, thus supporting the contention that both phosphoglycerides and triacylglycerols serve as depot lipids in this species of krill.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton

Prinsipper, problemer og praksis i Antarktis-utviklingen - Sollie, Finn (Internasjonal politikk, 1985)
Keywords: Antarktis; politikk

Dyr og planter på nunataker i Dronning Maud Land - Sømme, Lauritz (Det norske videnskaps-akademi. Årbok, 1985)
Keywords: Dronning Maud Land; biologi; insekter; petreller

Ecological studies on Cryptopygus sverdrupi from Muhlig-Hofmannfjella, Antarctica - Sømme, Lauritz (Cryo-Letters, 1985)
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

Resting spore formation in the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo - Syvertsen, Erik E. (Polar Biology, 1985)
The resting spore morphology of the antarctic diatoms Coscinodiscus furcatus Karsten and Thalassiosira australis Peragallo are described. Both species form endogenous resting spores. The spore valve of C. furcatus differ from those of the vegetative cells primarily by (i) a greater convexity and (ii) a coarser and more distinctly fasciculated areolation. This resting spore is identical to the diatom traditionally identified as C. stellaris var. symbolophorus (Grunow) Jørgensen in the Antarctic. The resting spore of T. australis differs from the vegetative cells by (i) a lack of clusters of strutted processes in a modified ring on valve face, (ii) a coarser areolation and tangential rows of areolae and (iii) a narrower and more simply structured girdle. The resting spore valve of T. australis has been described as belonging to a separate species, Actinocyclus excentricus Peragallo.
Keywords: Sørishavet; diatomeer; marinbiologi